2017 39th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2017
DOI: 10.1109/embc.2017.8037364
|View full text |Cite
|
Sign up to set email alerts
|

The role of nonmotor brain regions during human motor control

Abstract: Neural prostheses have generally relied on signals from cortical motor regions to control reaching movements of a robotic arm. However, little work has been done in exploring the involvement of nonmotor cortical and associative regions during motor tasks. In this study, we identify regions which may encode direction during planning and movement of a center-out motor task. Local field potentials were collected using stereoelectroencephalography (SEEG) from nine epilepsy patients implanted with multiple depth el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…The insula is known to be involved in the execution of arm movements in the gravitational field 92 . The insular cortex and temporal pole were shown to encode movement direction in a center-out motor task 93 , and the middle temporal gyrus was shown to be involved in encoding path-related information during a center-out motor task 94 . The involvement of nonmotor regions such as insula, temporal pole and the middle and superior temporal gyri point to their role in adaptive remapping processes supporting recovery 95 .…”
Section: Discussionmentioning
confidence: 99%
“…The insula is known to be involved in the execution of arm movements in the gravitational field 92 . The insular cortex and temporal pole were shown to encode movement direction in a center-out motor task 93 , and the middle temporal gyrus was shown to be involved in encoding path-related information during a center-out motor task 94 . The involvement of nonmotor regions such as insula, temporal pole and the middle and superior temporal gyri point to their role in adaptive remapping processes supporting recovery 95 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies that have attempted to decode patterns in sEEG data related to movement without machine learning have had mixed results. Attempts to decode movement direction (Johnson et al, 2017) and path information (Breault et al, 2017) have found few modulated areas and correlations that reached statistical significance but were on the order of r =0.2. A study decoding movement speed that used a more complex classification method, least absolute shrinkage and selection operator (LASSO) linear regression, had a higher correlation of r= 0.4 on average but with a large range of correlations across subjects and a mean squared error greater than one (Breault et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…These stereoelectroencephalography (sEEG) recordings provide an opportunity to determine the spatial extent of movement-related oscillations in humans because they sample a broad range of brain areas, including deeper regions. Previous sEEG studies found that movement direction (Johnson et al 2017) and movement path direction, deviation, and speed (Breault et al 2017) had statistically-significant correlations with beta power in a few brain areas, which were on the order of r = 0.2, reflecting modest predictive power at a single-trial resolution. Another study decoding movement speed that used a more complex classification method, least absolute shrinkage and selection operator linear regression, had a higher correlation of r = 0.4 on average using the entire sEEG electrode implantation montage for a patient, but had a large range of correlations across patients and a mean squared error greater than one (Breault et al 2019).…”
Section: Introductionmentioning
confidence: 91%